Effect of the number of incubated eggs and nurturing squabs on the behaviour and performance of breeding pigeons - Gharib, Heba S.A.; Dawod, Esraa H.; Youssef, Mohamed Y.I.; Saleem, Al Sadik K.Y.; Abdelaty, Asmaa I. (Journal of Advanced Veterinary Research, 2024)
The objective of this study was to evaluate the incubated egg and nurturing squab numbers on breeding pigeon behaviour and performance. Fifteen pairs of mature Egyptian Baladi Pigeons (12-18 months) were divided into 3 groups (one pair x 5 replicates for each group). Group1 (G1): each pair incubated one egg and reared one squab, Group2 (G2): parents incubated 2 eggs and reared 2 squabs and Group3 (G3): incubated 3eggs and reared 3 squabs. Maintenance and reproductive behaviour were recorded for each pair of parents using a digital camera and then analysed. In addition, the performance of adults and brooded squabs was evaluated. Results showed that the frequency of foraging and walking behaviour of females was significantly higher in G3. On the other hand, the other comfort behaviour was significantly higher for both parents in G1 compared to other groups indicating more welfare they had. No a significant impact was observed on other maintenance behaviour of breeding pigeons. Nest defence behaviour and prolactin level were increased with increasing the reared chicks or incubated eggs, while nest building was significantly decreased. Besides the prolonged incubation period & egg laying intervals in G3, the body weight (at 7 days old) and body weight gain (BWG) of squab at 7 and 14 days old declined significantly. A significant increase in body weight loss of female and male with increasing the number of reared chicks, moreover, raising the prolactin level in G3 compared to G1&G2. It concluded that, neither adult behaviour nor squab performance were adversely affected by increasing nurturing squab or incubated egg up to 3 squabs or 3 eggs which could be recommended practice for raising the economic profit in addition to feed supplements for a breeding pigeon to alleviate the loss in body mass at brooding period.